EFFECTIVENESS OF DIFFERENTIAL TEACHING METHODS AND MIXED LEVEL CLASSES - Xaydarova Shoira; Berdimurodova Dildora Qaxramon qizi (TADQIQOTLAR, 2026)
Annotation: This article examines the effectiveness of differentiated teaching methods in mixed level classrooms,where students demonstrate varying abilities,learning styles,and academic needs.The study highlights how differentiated instruction through flexible grouping, varieted task,adaptive materials,and learner- centered strategies —can enhance student engagement, motivation, and academic achievement. Special attention is given to the role of teachers in identifying individual differences and designing inclusive learning environments that support both high- achieving and struggling learners. The findings suggest that differentiated teaching methods contribute to more equitable learning outcomes, improved classroom interaction, and the development of learners’ autonomy. The article concludes that, despite certain challenges such as increased planning time and classroom management demands, differentiated instruction remains an effective approach for addressing diversity in mixed-level classes.